2018
DOI: 10.3389/fimmu.2018.02379
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition Receptors and the Host Cell Death Molecular Machinery

Abstract: Pattern Recognition Receptors (PRRs) are proteins capable of recognizing molecules frequently found in pathogens (the so-called Pathogen-Associated Molecular Patterns—PAMPs), or molecules released by damaged cells (the Damage-Associated Molecular Patterns—DAMPs). They emerged phylogenetically prior to the appearance of the adaptive immunity and, therefore, are considered part of the innate immune system. Signals derived from the engagement of PRRs on the immune cells activate microbicidal and pro-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
388
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 547 publications
(400 citation statements)
references
References 241 publications
(208 reference statements)
2
388
0
10
Order By: Relevance
“…Consistently, our current results also showed that TNBS induced TGF-b increase in the colon, and oral administration of the compounds significantly reduced the level of TGF-b with the best effects of 14n, 14k, 14c, and 14j. The innate immune system is activated by the pattern recognition receptors (PRRs) which recognise pathogen-associated molecular patterns (PAMPs) or endogenous danger-associated molecular patterns (DAMPs) generated during cellular injury or tissue damage [40][41][42] . PRRs comprise the membrane-bound toll-like receptors (TLRs) and the cytosolic sensory protein complexes such as NOD-like receptors (NLR) 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, our current results also showed that TNBS induced TGF-b increase in the colon, and oral administration of the compounds significantly reduced the level of TGF-b with the best effects of 14n, 14k, 14c, and 14j. The innate immune system is activated by the pattern recognition receptors (PRRs) which recognise pathogen-associated molecular patterns (PAMPs) or endogenous danger-associated molecular patterns (DAMPs) generated during cellular injury or tissue damage [40][41][42] . PRRs comprise the membrane-bound toll-like receptors (TLRs) and the cytosolic sensory protein complexes such as NOD-like receptors (NLR) 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The innate immune response is the first line of defense against invading pathogens and numerous mechanisms are in place to detect and respond to such threats. All cells are equipped with unique proteins that function as sensors called patternrecognition receptors (PRRs) which detect conserved parts of pathogens, termed Pathogen-Associated Molecular Patterns (PAMPs), or molecules that are released by damaged cells called Damage-Associated Molecular Patterns (DAMPs) (reviewed in Amarante-Mendes et al, 2018). There are several classes of PRRs including Toll-like receptors (TLRs), retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs) and NOD-like receptors (NLRs) that are stimulated during viral infections (Akira et al, 2006).…”
Section: Innate Immune Response and Enterovirus Countermeasuresmentioning
confidence: 99%
“…The innate immune system is the first line of defense against pathogens and it is comprised of cellular and molecular mechanisms that always act in a similar way against infection. All cellular components of the innate immune system have the ability to recognize microbial or damage-associated molecular patterns (known as PAMPs and DAMPs) via pattern recognition receptors (PRRs) or via specific proteins such as the complement system (27). Knowing that in HELLP syndrome several organs are affected and can serve as a source of DAMPs (28,29), it is interesting to know to what extent each of the innate immune components are involved in its etiopathogenesis.…”
Section: Innate Immune Component In Hellpmentioning
confidence: 99%